Valorization of Hazelnut Biomass Framework in Turkey: Support and Model Guidelines from the Italian Experience in the Field of Renewable Energy (International Journal of Sustainable Energy and Environmental Research, 2014)
In this study, we illustrate the results which were obtained using a comparative protocol concerning hazelnut production framework with special references to Turkey and Italy. Investigation includes supply, exports and several internal organization patterns. Emphasis was laid on proposing agro-forest biomass derived by hazelnut cultivations for renewable energy production via small-scale applications, in order to enhance farmers’ income within Turkish individual agro-districts. Due to importance of Turkey in world hazelnut trade, it is interesting to project some enhancements which have been already carried out in Italy. A consolidated protocol using DEA analyses gave evidence to the possibility of stabilizing both domestic and world prices along with differentiating hazelnut farmer’s income.